2020
DOI: 10.1126/sciadv.abb2454
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 mediates tubulation and vesicle sorting from lysosomes

Abstract: Genetic variation around the LRRK2 gene affects risk of both familial and sporadic Parkinson’s disease (PD). However, the biological functions of LRRK2 remain incompletely understood. Here, we report that LRRK2 is recruited to lysosomes after exposure of cells to the lysosome membrane–rupturing agent LLOME. Using an unbiased proteomic screen, we identified the motor adaptor protein JIP4 as an LRRK2 partner at the lysosomal membrane. LRRK2 can recruit JIP4 to lysosomes in a kinase-dependent manner via the phosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
200
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(235 citation statements)
references
References 63 publications
13
200
1
Order By: Relevance
“…Second, we were able to control the activation state of cells, which again would be impossible to perform in the human brain. Here, we extend our recent observation that lysosomal damage can activate the LRRK2 signaling pathway (24) to show that activation can occur in iMicroglia and that activation shows interaction with genotype. Given results from other laboratories that inflammatory signaling can promote LRRK2 activation through a similar pathway (30), we infer that neuroinflammation may interact with genotype at LRRK2, and potentially at other lysosomal genes associated with PD (31), to influence overall brain phenotype.…”
Section: The Rs76904798 Variant Does Not Drive the Observed Lrrk2 Eqtsupporting
confidence: 80%
See 1 more Smart Citation
“…Second, we were able to control the activation state of cells, which again would be impossible to perform in the human brain. Here, we extend our recent observation that lysosomal damage can activate the LRRK2 signaling pathway (24) to show that activation can occur in iMicroglia and that activation shows interaction with genotype. Given results from other laboratories that inflammatory signaling can promote LRRK2 activation through a similar pathway (30), we infer that neuroinflammation may interact with genotype at LRRK2, and potentially at other lysosomal genes associated with PD (31), to influence overall brain phenotype.…”
Section: The Rs76904798 Variant Does Not Drive the Observed Lrrk2 Eqtsupporting
confidence: 80%
“…In this cell model, we could measure LRRK2 kinase activity based on the phosphorylation of physiological substrate Rab10 (23). As well as baseline activity, we explored methods of microglia stimulation and LRRK2 activation by exposing cells for two hours to lipopolysaccharide (LPS), α-synuclein conditioned medium (aSCM), or L-leucyl-L-leucine methyl ester (LLOMe), which we have recently shown to activate LRRK2 in primary mouse astrocytes (24). Immunoblot analysis indicated that of the three treatments, LLOMe most strongly activated LRRK2 kinase activity in iMicroglia as measured by significantly increased phosphorylation of Rab10 ( Fig.…”
Section: Ipsc-derived Microglia Are Transcriptionally Similar To Braimentioning
confidence: 99%
“…It would be interesting to explore whether these agonists promote the recruitment of LRRK2 to particular membrane compartments, thereby activating LRRK2 and promoting Rab10 and Rab12 phosphorylation at that location. Recruitment of LRRK2 to membranes has been proposed previously to be a key mechanism by which LRRK2 activity is regulated [ 29 , 57 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that pharmacological manipulations that induce lysosomal damage trigger LRRK2 translocation to lysosomes and lead to an increase in Rab phosphorylation (26,27). Further, LRRK2 expression in immune cells is elevated in response to various inflammatory stimuli such as IFN- (28)(29)(30).…”
Section: High Lrrk2 Expression and Activity Are Observed In Mouse Glimentioning
confidence: 99%